2011
DOI: 10.1002/sia.3758
|View full text |Cite
|
Sign up to set email alerts
|

Interface analysis of Ti/Al/Ti/Au ohmic contacts with regrown n+‐GaN layers using molecular beam epitaxy

Abstract: The regrowth technique of highly doped n-type GaN layers is reliable and effective for lowering the ohmic contact resistance. The interface between metal contacts with Ti/Al/Ti/Au and regrown n + -GaN/GaN layers were analyzed in detail with transmission electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Our technique was also shown to be more effective than ion implantation to improve the Ohmic contact properties [16,17]. In this work, the detailed study of the interface between nonalloyed contact metals and the regrown GaN is performed and compared with the conventional alloyed counterpart using X-ray diffraction (XRD), scanning transmission electron microscopy (STEM), Auger electron microscopy (AES) and scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…Our technique was also shown to be more effective than ion implantation to improve the Ohmic contact properties [16,17]. In this work, the detailed study of the interface between nonalloyed contact metals and the regrown GaN is performed and compared with the conventional alloyed counterpart using X-ray diffraction (XRD), scanning transmission electron microscopy (STEM), Auger electron microscopy (AES) and scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we were able to realize SAG by PAMBE, achieving a record low contact resistivity of 1.8 Â 10 À8 V cm 2 and much enhanced peak drain currents for both GaN MESFET and HEMT [9,10]. We also demonstrated that unlike ion implantation, the damage-free PAMBE-SAG technique is able to suppress the buffer leakage current and improve the breakdown characteristics [11][12][13]. Due to the simultaneous improvement of drain current and breakdown voltage, PAMBE-SAG is most suited to fabricate high power transistors.…”
mentioning
confidence: 99%